Efficient Removal of Non-Structural Protein Using Chloroform for Foot-and-Mouth Disease Vaccine Production - Park, Sun Young (Vaccines (Basel), 2020)
To differentiate foot-and-mouth disease (FMD)-infected animals from vaccinated livestock, non-structural proteins (NSPs) must be removed during the FMD vaccine manufacturing process. Currently, NSPs cannot be selectively removed from FMD virus (FMDV) culture supernatant. Therefore, polyethylene glycol (PEG) is utilized to partially separate FMDV from NSPs. However, some NSPs remain in the FMD vaccine, which after repeated immunization, may elicit NSP antibodies in some livestock. To address this drawback, chloroform at a concentration of more than 2% (v/v) was found to remove NSP efficiently without damaging the FMDV particles. Contrary to the PEG-treated vaccine that showed positive NSP antibody responses after the third immunization in goats, the chloroform-treated vaccine did not induce NSP antibodies. In addition to this enhanced vaccine purity, this new method using chloroform could maximize antigen recovery and the vaccine production time could be shortened by two days due to omission of the PEG processing phase. To our knowledge, this is the first report to remove NSPs from FMDV culture supernatant by chemical addition. This novel method could revolutionize the conventional processes of FMD vaccine production.